كتب السيرة النبوية للأطفال في الأدب العربي والأردي من م1975 إلى 2010م: Books of Seerat Studies in Arabic Literature & Urdu (1975-2010) - Dr. Nargis Nazeer,; Dr. Sarwat Jameela, (MEI, 2023)
This article, entitled "Books of the Prophetic Biography for Children in Arabic and Urdu Literature from 1975 to 2010", deals with a review of the most important and prominent books of the Prophetic Biography for Children in Arabic and Urdu, which were written during the mentioned time period, It presented the information of each book briefly, i.e. name of the author and title of the book ,its place of publication and year, and the summary of the contents of each book.